Endocan and Soluble Triggering Receptor Expressed on Myeloid Cells-1 as Novel Markers for Neonatal Sepsis - Mehmet Saldir; Turan Tunc; Ferhat Cekmez; Merih Cetinkaya; Tugce Kalayci; Kursat Fidanci; Oguzhan Babacan; Galip Erdem; Necmettin Kocak; Erkan Sari; Emin Ozgur Akgul; Mustafa Kul (Elsevier, 2015)
Neonatal sepsis is an important cause of neonatal morbidity and mortality in the neonatal intensive care unit. Soluble triggering receptor expressed on myeloid cells-1 (sTREM-1) has been evaluated in sepsis and septic shock, and it was found to be valuable in distinguishing septic cases from nonseptic cases. Endocan is constitutively expressed by endothelial cells, and high levels of endocan may be of relevance for the promotion of systemic inflammation. The aim of this study was to investigate whether the levels of sTREM-1 and endocan were increased in late-onset neonatal sepsis. Methods: Patients were classified into septic and nonseptic groups. Blood was collected from a peripheral vein of all septic newborns and healthy newborns at the time of initial laboratory evaluation before any treatment, and within 48-72 hours after initiation of treatment. Serum sTREM-1 and endocan measurements were performed when the study was finished. Results: The study population comprised of 50 neonates: 20 nonseptic neonates and 30 septic neonates. The groups were similar with regards to baseline characteristics. The initial measurements of interleukin-6 (IL-6), sTREM-1, endocan, and immature/total neutrophil ratio (I/T ratio) were significantly higher in septic neonates in comparison with nonseptic neonates. Receiver operating characteristic (ROC) curve analyses revealed that IL-6, sTREM-1, endocan, and I/T ratio resulted in significant areas under the curve (AUC) with respect to early identification of septic neonates. Soluble TREM-1 and IL-6 performed best to distinguish septic neonates from nonseptic neonates. Univariate logistic regression analysis showed that increased IL-6 and sTREM-1 were strong predictors of neonatal late-onset sepsis. Conclusion: Serum sTREM-1, IL-6, endocan levels, and I/T ratio increased in septic neonates. However, the diagnostic accuracy of circulating sTREM-1 seemed to be better than endocan and I/T ratio, but lower than IL-6.